-17=-2n-13-8n

Simple and best practice solution for -17=-2n-13-8n equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -17=-2n-13-8n equation:


Simplifying
-17 = -2n + -13 + -8n

Reorder the terms:
-17 = -13 + -2n + -8n

Combine like terms: -2n + -8n = -10n
-17 = -13 + -10n

Solving
-17 = -13 + -10n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '10n' to each side of the equation.
-17 + 10n = -13 + -10n + 10n

Combine like terms: -10n + 10n = 0
-17 + 10n = -13 + 0
-17 + 10n = -13

Add '17' to each side of the equation.
-17 + 17 + 10n = -13 + 17

Combine like terms: -17 + 17 = 0
0 + 10n = -13 + 17
10n = -13 + 17

Combine like terms: -13 + 17 = 4
10n = 4

Divide each side by '10'.
n = 0.4

Simplifying
n = 0.4

See similar equations:

| -4x-33=42-9x | | (14x-1)+(8x-7)=78 | | 20t+.15=30t+.10 | | 6y+12+2y=5y-2 | | 61=2x+17+x+17 | | 2n=10.06 | | 70=7x | | (2x-5)=-6 | | 9.5=v+2.8 | | 8x-6=3x+24 | | (2x-5)=6 | | 15x-8x=49 | | 12*c=108 | | 7y+8=-2y | | 2v+28=16+-4(v+7) | | -2(g+8)=64 | | -2-m=7 | | 4x^2=3x^2+9 | | 5(f-4)=-10 | | -5+5x=35 | | (x-2)=-2x-1 | | 8g-32=4g+16 | | X+17+4x=-29-4x-35 | | 1halfr+6=3-2r | | -10(s+3)=-71 | | (5x^3-6x^2+2x)+(-4x^2+3x)=42 | | 35x^2+76x+32= | | -10(s+3)=71 | | (x-5)=-6x-10 | | 3-2x^2=21 | | 10=-0.15x^2+3x | | t+10=7t+4 |

Equations solver categories